Investigation of Naoluoxintong on the neural stem cells by facilitating proliferation and differentiation in vitro and on protecting neurons by up-regulating the expression of nestin in MCAO rats. (5th December 2022) - Hong, Lu; Jiang, Huihui; Liu, Mingming; Zhao, Guodong; Shi, Xiaoqian; Tan, Hui; Peng, Daiyin; Wang, Lei; Chen, Weidong; He, Ling
Abstract: Ethnopharmacological relevance: The classic traditional Chinese compound Naoluoxintong (NLXT) has been proven an effective remedy for ischemic stroke (IS). The protective effect of NLXT on neural stem cells (NSCs), however, remains unclear. Aim of the study: To investigate the protective effect of NLXT on NSCs in rats with middle cerebral artery occlusion (MCAO) and the effect of Nestin expression in vivo . Materials and methods: Sprague-Dawley (SD) rats were randomly divided into three groups: the sham-operated group, the MCAO model group and the NLXT group. The MCAO model in rats was established by modified Longa wire embolization method. The sham-operated group, the model group and the NLXT groups were divided into three subgroups according to the sampling time points of 1 d, 3 d and 7 d after successful model-making. Immunofluorescence staining, including bromodeoxyuridine (BrdU)/glial fibrillary acidic protein (GFAP), β-tubulinIII/GFAP, BrdU/doublecortin (DCX) and BrdU/neuronal nuclei (NeuN), was used to detect the proliferation and survival of NSCs in the hippocampal after drug administration. Protein expression of Nestin, DCX, GFAP and NeuN in the hippocampal was detected by Western blot (WB). Results: Immunofluorescence experiment of Nestin labeled: on the first day, a few Nestin-positive cells were found in the hippocampal DG area. Afterwards, the number of Nestin-labeled positive cells in the model group increased, while the number of cells in the sham group did not fluctuate significantly. The number of positive cells in each administration group increased more than that in the model and normal group. β-tubulin III/GFAP double-labeled: a small amount of double labeled cells was expressed in the normal group, and the number subsequently fluctuated little. In the model group, β-tubulin III/GFAP positive cells increased initially after acute ischemia, and gradually decreased afterwards. In the NLXT-treated group, β-Tubulin III positive cells were significantly increased on day 1, 3 and 7, while GFAP positive cells had little change. BrdU/DCX double-labeled: initially, a small number of BrdU/DCX-labeled positive cells were observed in the normal group and the model group, but there was no increasing trend over time. The positive cells in the NLXT group increased over time, and those in the seven-day group were significantly higher than those in the one-day and three-day groups. BrdU/NEUN double-labeled: in the normal group, BrdU/NEUN positive cells were enriched and distributed regularly. The number of positive cells in the model group was small and decreased gradually with time, and the decrease was most obvious on the third day. The number of positive cells in the NLXT group was significantly higher than that in the model group, and the number of positive cells in the seven-day group was significantly higher than that in the one-day and three-day groups. WB results reflected those three proteins, Nestin, NeuN and DCX, showed an increase in expression, except GFAP, which showed a decreasing trend. Conclusions: Preliminarily, NLXT can promote the migration and differentiation of NSCs. It may have a protective effect on the brain by promoting repair of brain tissue damage through upregulation of Nestin after IS. Graphical abstract: Image 1 Highlights: The curative effect of Naoluoxintong (NLXT) in treating ischemic stroke clinically is accurate, but, its protective mechanism is unclear. The article revealed the protective mechanism of NLXT on the neural stem cells by facilitating proliferation and differentiation in vitro and on protecting neurons by up-regulating the expression of Nestin in MCAO rats.